The complexity of the meat supply chain in Cameroon: Multiplicity of actors, interactions and challenges - Victor Tsapi; Marie-Noël Assene; Hans-Dietrich Haasis (Logistics, 2022)
Background: Beef, because of its high protein content, occupies a privileged place in household consumption in Cameroon. However, the quality of the meat available on the market and the prices charged are far from satisfactory for consumers. There is therefore clearly a problem of physical and financial accessibility to quality beef for the Cameroonian consumer (in a country where 37.5% of the population lives below the poverty line). Methods: To analyze this problem, a qualitative exploratory study based on interviews and on-site observations was conducted. Results: In the article, we are interested in the Supply Chain (SC) of beef in Cameroon, with the aim of understanding its dynamics and highlighting the main obstacles that prevent the actors involved from ensuring consumers, the availability of quality meat at a reasonable price. Through the qualitative exploratory study conducted with the main actors involved (breeders, livestock traders, modern and traditional slaughterhouses, butchers, etc.), we show that the SC of beef in Cameroon is plagued by technical, financial, managerial and cultural constraints that prevent them from satisfying their customers and to take full advantage of their activities. Conclusions: Despite the methodological limits related to sampling and an essentially qualitative approach, the quality and richness of the information collected through in-depth interviews edify the main difficulties and challenges encountered by the actors and lead to managerial implications and prospects of research.
Keywords: 650; beef industry; meat supply chain; meat trade; supply chain interactions